Soil Degradation, Soil Pollution and Ecological Restoration - Sun, Bo; Liu, Ming; Chen, Yan (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Soil degradation is a complex phenomenon that can result in a diminished capacity of the ecosystem to provide goods and services for its beneficiaries. Degraded soils have a health status such that they do not provide the normal goods and services of the particular soil in its ecosystem. Ecological rehabilitation is required when the soil is degraded to such an extent that the land becomes unproductive. Soil degradation can be caused by various factors, including physical aspects such as soil sealing and crusting, soil erosion, and soil compaction, which may result in severe landscape deterioration. Soil nutrient imbalance or depletion is also a widespread cause of soil degradation due to inappropriate practices in agricultural areas. Acidification, alkalization, and salinization are also serious problems of soil degradation. In addition to physical and chemical soil degradation, the biological health of the soil can be damaged as well. In recent decades, toxic contamination of soil, for instance, heavy metal pollution, organic pollutant contamination, etc., has brought more pressing issues. Therefore, effective and up-to-date technology for soil degradation and soil pollution restoration is urgently needed. The goal of this Special Issue was to establish a platform for researchers to communicate research results or the latest insights in related fields.